Modern monetary theory and paractice: an introductory text - Mitchell, William; Wray, L. Randall; Watts, Martin J. (University of Newcastle, 2016)
"Modern Monetary Theory and Practice: An Introductory Text is an introductory textbook for university-level macroeconomics students. It is based on the principles of Modern Monetary Theory (MMT) and includes the following detailed chapters: Chapter 1: Introduction Chapter 2: How to Think and Do Macroeconomics Chapter 3: A Brief Overview of the Economic History and the Rise of Capitalism Chapter 4: The System of National Income and Product Accounts Chapter 5: Sectoral Accounting and the Flow of Funds Chapter 6: Introduction to Sovereign Currency: The Government and its Money Chapter 7: The Real Expenditure Model Chapter 8: Introduction to Aggregate Supply Chapter 9: Labour Market Concepts and Measurement Chapter 10: Money and Banking Chapter 11: Unemployment and Inflation Chapter 12: Full Employment Policy Chapter 13: Introduction to Monetary and Fiscal Policy Operations Chapter 14: Fiscal Policy in Sovereign nations Chapter 15: Monetary Policy in Sovereign Nations It is intended as an introductory course in macroeconomics and the narrative is accessible to students of all backgrounds. All mathematical and advanced material appears in separate Appendices."